Probiotic supplementation modulates the gut microbiome and improves clinical outcomes in pediatric refractory asthma - Liu, Zheng; Deng, Wen; Xu, Wenlin; Ye, Linlin; Rao, Zhihui (Frontiers in Microbiology, 2026)
BackgroundRefractory asthma in children remains a clinical challenge despite conventional therapies, with emerging evidence linking gut microbiome dysbiosis to persistent inflammation via the gut-lung axis. This study investigated whether multi-strain probiotic supplementation could improve asthma control and restore microbial balance when added to standard treatment.MethodsThis prospective randomized controlled trial enrolled 88 children aged 4–8 years with refractory asthma. Participants were allocated into two groups (n = 44 each): a conventional treatment group (bronchodilators and glucocorticoids) and a combination treatment group, which received conventional therapy plus a multi-strain probiotic (Bifidobacterium, Lactobacillus acidophilus, Streptococcus thermophilus) for 4 months. Primary outcomes were asthma control level, Asthma Control Test (ACT) scores, and pulmonary function (FEV₁, FVC, PEF). Secondary outcomes included gut microbiota changes, assessed by 16S rRNA gene sequencing.ResultsCombination therapy achieved complete asthma control in 68.18% of patients versus 36.36% with conventional therapy (Z = 2.415, p < 0.05). Post-treatment ACT scores were higher in the combination group (22.45 ± 1.20 vs. 19.78 ± 1.45; p < 0.05), with superior improvements in FEV1 (2.65 ± 0.10 L vs. 2.30 ± 0.08 L; p < 0.001), FVC (3.10 ± 0.18 L vs. 2.80 ± 0.15 L; p < 0.001), and PEF (4.00 ± 0.25 L/s vs. 3.50 ± 0.20 L/s; p < 0.001). Symptoms resolved faster with combination therapy (e.g., cough: 5.60 ± 1.50 vs. 10.45 ± 2.30 days; p < 0.05). Microbiome analysis showed increased alpha diversity (e.g., Shannon index: p < 0.05) and beneficial shifts in the combination group, including higher Bifidobacterium (25.00 ± 15.31% vs. 0.98 ± 1.92%; p < 0.001) and reduced Bacteroides, with distinct beta diversity clustering (PERMANOVA p < 0.05).ConclusionAdjunctive multi-strain probiotics enhance clinical outcomes and gut microbiome health in pediatric refractory asthma, supporting microbiome-targeted therapies via the gut-lung axis. Larger, double-blind randomized controlled trials are warranted to confirm long-term benefits.